Clinical Efficacy, Antibiotic Resistance Genes, Virulence Factors and Outcome of Hospital-Acquired Pneumonia Induced by Klebsiella pneumoniae Carbapenemase 2-Producing with Tigecycline Treatment in the ICU - Bai XR; Cao JR; Wang ZZ; Li WC; Chen DD; Lou R; Qu X; Yan SY (Infection and Drug Resistance, 2022)
Xiang-Rong Bai,1,* Jing-Rong Cao,2,* Zhi-Zhou Wang,1 Wen-Chao Li,1 Dian-Dian Chen,2 Ran Lou,3 Xin Qu,4 Su-Ying Yan1 1Department of Pharmacy, Xuan Wu Hospital Capital Medical University, National Gerontic Disease Clinical Research Center, Beijing, 100053, People’s Republic of China; 2Department of Clinical Laboratory, Xuan Wu Hospital Capital Medical University, National Gerontic Disease Clinical Research Center, Beijing, 100053, People’s Republic of China; 3Department of Intensive Medicine, Xuan Wu Hospital Capital Medical University, National Gerontic Disease Clinical Research Center, Beijing, 100053, People’s Republic of China; 4Intensive Care Unit, Department of Neurosurgery, Xuan Wu Hospital Capital Medical University, National Gerontic Disease Clinical Research Center, Beijing, 100053, People’s Republic of China*These authors contributed equally to this workCorrespondence: Su-Ying Yan, Department of Pharmacy, Xuan Wu Hospital Capital Medical University, National Gerontic Disease Clinical Research Center, No. 45 Changchun Street, Xi Cheng District, Beijing, 100053, People’s Republic of China, Tel/Fax +86 10-63012837, Email yansuying10@sina.cnPurpose: Tigecycline is an agent for carbapenemase-producing Klebsiella pneumonia (KPC-KP), given its penetration into lung tissues. Our study focused on the molecular and clinical efficacy of tigecycline for hospital-acquired pneumonia (HAP) in the ICU.Patients and Methods: A retrospective cohort study of 52 adult KPC-KP HAP patients by searching hospital medical records from January 2018 to December 2020 was established to investigate the epidemiology of KPC-KP infections for tigecycline treatment and the associated clinical efficacy of tigecycline. The KPC-KP isolates underwent multilocus sequence typing. Molecular typing, antimicrobial resistance, and virulence profiling were also analyzed by whole-genome sequencing of KPC-KP.Results: Among 52 patients with KPC-KP, the ICU mortality rate was 14/52 (27%), and there was no significant statistical difference in mortality between the effective group and failure group (p = 0.754). However, the duration of tigecycline was statistically different between the two groups of patients (14.4 vs 10 days, p=0.046). The total bacterial clearance rate was 6/52 (11.5%). There was no significant statistical difference in both groups (p=0.416). Antibiotic resistance genes (aac3iia) and virulence gene (AREO-iutA, Capsule-wzc) were negatively correlated with clinical efficacy (p = 0.011, OR = 1.237).Conclusions: Blakpc was the main carbapenemase in all K. pneumoniae strains. ST11-KL64 KPC-KP was the most common virulence factors in KPC-KP isolates. This study suggested that antibiotic resistance genes (aac3iia) and virulence gene (AREO-iutA, Capsule-wzc) were independent mortality risk factors for patients with Klebsiella pneumoniae carbapenemase-2 producing K. pneumoniae infections, when during the tigecycline treatment. Molecular analysis of K. pneumoniae may provide an option when choosing the antimicrobial treatment.Keywords: Klebsiella pneumoniae, carbapenemase, virulence factors, resistance genes, hospital-acquired pneumonia